YIELD OF SPUTUM INDUCTION WITH 3 % HYPERTONIC SALINE IN SMEAR NEGATIVE PULMONARY TUBERCULOSIS - AKHILESH KUNOOR; THITTA MOHANTY; M.R.PATTNAIK; D.P.DASH (International Journal of Pharma and Bio Sciences, 2016)
Tuberculosis continues as a major health problem all over the world. Sputum AFB is still the initial diagnostic strategy in Pulmonary Tuberculosis (TB) as it is cost effective, non invasive and easily accessible. But due to the lack of a proper specimen lot of suspected cases remain misdiagnosed and wrongly treated leading to unnecessary cost and side effects. Here we are trying to produce good quality of sputum to increase the yield of AFB smear for TB diagnosis by inducing sputum with 3% hypertonic saline.100 patients who had clinico-radiological suspicion of pulmonary tuberculosis having either initial sputum smear negative or inadequate sputum were included in the study. 91 patients produced adequate amount of sputum (>2 ml) after induction procedure.37 patients were found to be smear AFB positive after induction. Sputum induction with hypertonic saline produces good quality and adequate amount of sputum for smear examination thereby increasing the yield for smear positive pulmonary tuberculosis.